Antifungal Activity of Pare Leaf (Momordica charantia L.) Methanol Extract - Baiq Naili Dewi Atika (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2021)
Pare leaf (Momordica charantia L) is known to have potential as anti-bacterial and anti-fungal agent. This plant contains tannins, flavonoids, saponins, alkaloids, and triterpenoids. The administration of pare leaf methanol extract was hypothesized to increase inhibition zone in Candida albicans and Rhodotorulla sp colonies. The aim of this study was to determine antifungal activity of pare leaf methanol extract (PAME) against Candida albicans and Rhodotorulla sp. The method used in this study was well-diffusion method. Medium used for culture was MHA and each petri dishes was inoculated with suspension of either Candida albicans or Rhodotorulla sp., followed by making wells using sterilized straw. Pare leaf extract was added into each well at various concentration of 20%, 40%, 60%, 80%, 100%. Data was analyzed qualitatively based on the diameter of the inhibition zone to determine antifungal activity. The study was designed as an experiment with a completely randomized design. Results showed that the largest inhibitory zone was 12 mm at a concentration of 100% for inhibiting candida Albicans while for inhibiting Rhodotorulla sp was 8 mm. Statistical test produced a significant difference, indicating that pare (Momordica charantia L) leaf methanol extract was able to inhibit the growth of Candida albicans and Rhodotorulla sp.